Analisis Yuridis Normatif Pemberian Kompensasi Perjanjian Kerja Waktu Tertentu (PKWT) Berdasarkan Undang-Undang Cipta Kerja - Diah Puji Lestari (Jurnal Hukum Lex Generalis, 2022)
The dynamics of updating labor regulations need to be studied for the benefit of society in general, and workers/labourers in particular. Since the enactment of Law No. 11 of 2020, and Government Regulation No. 35 of 2021, there have been the deletion, renewal, and the insertion of new articles on labor law. Among these regulatory reforms, what is discussed in this study is focused on analyzing the rules for a Specific Time Work Agreement (PKWT) in the Job Creation Law. There is a change in the PKWT rules, namely that workers/laborers whose contract period has expired are entitled to receive compensation or severance pay. This is something new, so the purpose of this study is to analyze normatively the rules for providing compensation or severance pay, starting from the distribution of the amount, to the sanctions that the company gets if it violates it.